Facilities and Infrastructure in Childcare Management - Syafrimen Syafril; Pahrudin, Agus; Jatmiko, Agus; Kuswanto, Cahniyo Wijaya; Dian Resti Ningsih (Jurnal Pendidikan Anak Usia Dini Undiksha, 2022)
Childcare, more popularly called DayCare (DC), must be adequately packaged to create an ideal learning environment and meet care needs as long as the children are not with their parents. This study aims to analyze the standard management of facilities and infrastructure in daycare to be used as a reference in managing a quality daycare. A single case design qualitative approach (single unit holistic analysis) was used as the research method. Data were collected through observation and in-depth interviews with the head of a professional daycare center. The results are then analyzed thematically through data reduction, data presentation, and concluding with the help of NVivo 12.0 software. The study's results through observations and interviews found that the management of facilities and infrastructure had been carried out properly, such as planning needs, procurement, inventory, storage, maintenance, use and removal, and structuring of land, buildings, school equipment, and furniture. However, the research findings show a need for a management information system to monitor all student activities. Then if you want to create a quality childcare center, CCTV in every corner of the room must be equipped to see all the children's activities. This research implies that it provides interesting information and needs attention for all DCs.